Parental Migration Decisions and Child Health Outcomes: Evidence from China - Carl Lin; Yana van der Meulen Rodgers (Institute of Labor Economics (IZA), 2018)
This study uses migrant household survey data from 2008 and 2009 to examine how parental migration decisions are associated with the nutritional status of children in rural and urban China. Results from instrumental variables regressions show a substantial adverse effect of children's exposure to parental migration on height-for-age Z-scores of left-behind children relative to children who migrate with their parents. Additional results from a standard Blinder-Oaxaca decomposition, a quantile decomposition, and a counterfactual distribution analysis all confirm that children who are left behind in rural villages – usually because of the oppressive hukou system – have poorer nutritional status than children who migrate with their parents, and the gaps are biggest at lower portions of the distribution.
Keywords: I10; J61; 330; migration; China; children; health; nutrition